Inhibition of sodium-dependent phosphate transporter NaPi2b function with MX35 antibody - Gryshkova, V.S.; Filonenko, V.V.; Kiyamova, R.G. (Вiopolymers and Cell, 2011)
Sodium-dependent phosphate transporter NaPi2b is involved in transport of inorganic phosphate and the maintenance of phosphate homeostasisin human body. NaPi2b wasrecently identified as a marker of ovarian cancer,
termed MX35. Monoclonal antibody (mAb) against transporter NaPi2b, called MX35, demonstrated therapeutic
efficacy in radioimmunotherapy of patients with ovarian cancer. Aim. The present experiments explored whether MX35 antibody can affect function of NaPi2b to transport inorganic phosphate ions in cellular models.
Methods. HEK293 cells stably expressing wild type NaPi2b and mutant NaPi2b_T330V, which could not be recognized by MX35 antibody, were incubated with MX35 antibody and analyzed by phosphate uptake assay.
Results. Cells expressing wild type NaPi2b showed reduced phosphate uptake after incubation with MX35 antibody at concentration 50 µg/ml. No significant changes in phosphate transport were detected for cells expressing NaPi2b_T330V at the same experimental conditions. Conclusions. Our results demonstrate 1,8-fold decrease of NaPi2b-mediated phosphate transport in HEK293 cells stably expressing wild type NaPi2b after
MX35 antibody application, which can be considered as a specific inhibitor of NaPi2b function.
Keywords: NaPi2b, MX35 antibody. Натрій-залежний транспортер фосфату NaPi2b бере участь у
перенесенні неорганічного фосфату та підтриманні фосфатного гомеостазу в організмі людини. Нещодавно NaPi2b описано як
маркер раку яєчника МХ35. Моноклональні антитіла (МКАТ)
проти транспортера NaPi2b, які отримали назву МХ35, виявляють терапевтичну ефективність при лікуванні хворих на рак
яєчника. Мета даної роботи полягала в тому, щоб з’ясувати, чи
впливає зв’язування МКАТ МХ35 з NaPi2b на його функцію транспортувати іони неорганічного фосфату в клітинних моделях.
Методи. Клітини лінії НЕК293, що стабільно експресують дикий
тип NaPi2b та мутантну форму NaPi2b_T330V, яка не розпізнається антитілами МХ35, інкубували з антитілами МХ35,
після чого аналізували поглинання клітинами радіоактивно міченого фосфату. Результати. Після інкубації з антитілами МХ35
у концентрації 50 мкг/мл відмічено значне зменшення поглинання
фосфату клітинами, які експресують дикий тип NaPi2b. Для
клітин, що експресують мутантну форму NaPi2b_T330V, за аналогічних експериментальних умов значних змін у поглинанні фосфату не виявлено. Висновки. Наші дані свідчать про 1,8-разове зниження NaPi2b-залежного транспорту фосфату в результаті
інкубації з МКАТ МХ35, які можуть слугувати специфічним інгібітором функції NaPi2b.
Ключові слова: NaPi2b, моноклональні антитіла МХ35. Натрий-зависимый транспортер фосфата NaPi2b участвует в
переносе неорганического фосфата и поддержании фосфатного
гомеостаза в организме человека. Недавно NaPi2b описан как
маркер рака яичника МХ35. Моноклональные антитела (МКАТ)
против транспортера NaPi2b, названные МХ35, проявляют терапевтическую эффективность при лечении больных раком яичника. Цель данной работы состояла в выяснении того, влияет ли
связывание МКАТ МХ35 с NaPi2b на его функцию транспортировать ионы неорганического фосфата в клеточных моделях. Методы. Клетки линии НЕК293, стабильно экспрессирующие дикий
тип NaPi2b и мутантную форму NaPi2b_T330V, не распознаваемую антителами МХ35, инкубировали с антителами МХ35, после
чего анализировали поглощение клетками радиоактивно меченного фосфата. Результаты. После инкубации с антителами
МХ35 в концентрации 50 мкг/мл отмечено значительное уменьшение поглощения фосфата клетками, экспрессирующими дикий
тип NaPi2b. Для клеток, экспрессирующих мутантную форму
транспортера NaPi2b_T330V, не выявлено существенных изменений в поглощении фосфата при аналогичных экспериментальных условиях. Выводы. Наши результаты свидетельствуют о
1,8-кратном снижении NaPi2b-зависимого транспорта фосфата в результате инкубации с МКАТ МХ35, которые можно рассматривать как специфический ингибитор функции NaPi2b.
Ключевые слова: NaPi2b, моноклональные антитела МХ35.